Isolation and Identification of Microalgal Strains and Evaluation of Their Fatty Acid Profiles for Biodiesel Production - Anitha, S (International Journal of Pharmaceutical & Biological Archive, 2012)
Isolation and Identification of Microalgal Strains and Evaluation of Their Fatty Acid Profiles for Biodiesel Production